2022
DOI: 10.1111/jvp.13079
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of carprofen following single and repeated intravenous administrations of different doses in sheep

Abstract: The aim of this study was to determine the pharmacokinetics of carprofen following single and repeated intravenous (IV) administrations at 1.4 and 4 mg/kg doses in sheep. The study was carried out on twelve sheep in two experiments as single‐ and multiple‐dose pharmacokinetics. In experiment 1, carprofen was administered via IV at single doses of 1.4 (n = 6) and 4 mg/kg (n = 6) in a randomized parallel design. In experiment 2, the same dose groups in experiment 1 following the 21‐day washout period received in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Carprofen is used extra-label at doses of 2-4 mg/kg in goats [16,30]. Carprofen was well tolerated after single and repeated intravenous administration at a dose of 4 mg/kg to sheep [31,32]. It was reported that IV and extravascular (IM, oral, subcutaneous) t 1/2λz of carprofen in sheep were similar and peak plasma concentration was reached in 2.06-11.73 h after extravascular administration [27].…”
Section: Discussionmentioning
confidence: 99%
“…Carprofen is used extra-label at doses of 2-4 mg/kg in goats [16,30]. Carprofen was well tolerated after single and repeated intravenous administration at a dose of 4 mg/kg to sheep [31,32]. It was reported that IV and extravascular (IM, oral, subcutaneous) t 1/2λz of carprofen in sheep were similar and peak plasma concentration was reached in 2.06-11.73 h after extravascular administration [27].…”
Section: Discussionmentioning
confidence: 99%